Measuring Successful Leadership VIA A Seven Factor Model on Net Profit – A Case of Amazon in Commercial Banking Industry in Vietnam - Huu Tung, Phuong; Tran Ngoc Huy, Dinh; Thi Thanh, Le; Van Tri, Nguyen; Gia Tho, Nguyen; Truong Linh, Thuong (International Journal of Psychosocial Rehabilitation, 2020)
Since 2019, Amazon, the e-commerce giant, has surpassed Walmart, becoming the largest retailer in the world. It has made very positive contributions to the overall achievements of the online retail industry, deserving of its position as one of the leading retailers in the US. Movement of stock price in the retail industry in developed countries such as the USA will reflect the business health of the retail system and the whole economy. Good business management requires us to consider the impacts of multiple micro and macro factors on stock price, and it contributes to promoting business plans and economic policies for economic growth and stabilizing macroeconomic factors. By data collection methods through statistics, analysis, synthesis, comparison, and quantitative analysis to generate qualitative comments and discussion, using econometric methods to perform regression equations and evaluate quantitative results, the article analyzed and evaluated the impacts of SEVEN (7) micro- and macroeconomic factors such as stock price, risk-free rate, lending rate, inflation, US GDP growth, S&P 500, cost, net profit, etc. on the net profit of an e-commerce giant, Amazon (AMZN), in the US in the period of 2014-2019, both positive and negative sides. The results of quantitative research, in a seven-factor model, show that the decrease in inflation, GDP, and cost reduction and increasing sales have a significant effect on improving AMZN's net profit with the highest impact coefficient; the second is decreasing stock price. This research finding and recommended policy also can be used as a reference in policy for the company and retail industry.